Faktor-faktor yang Mempengaruhi Kepuasan Nasabah - Oktaviana Vivi P; Tantri Widiastuti; Suhaji Suhaji (STIE Widya Manggala, 2021)
This study aimed to determine the effect of price and service quality on customer satisfaction at PT. Asuransi Sequis Life Semarang. The population used in this study were all policyholder customers or customers who had purchased Sequis Life insurance at Semarang Branch, while the total sample was 53 respondents. The sampling technique used in this study was purposive sampling. The data used were primary data obtained from the questionnaire, while the analytical tool used was multiple linear regression analysis. The results showed that price had a positive and significant effect on customer satisfaction, and service quality had a positive and significant effect on customer satisfaction.